Corona effect in frequency dependent transmission line models - De Freitas, Michelly Alcantara; Kurokawa, Sérgio [UNESP]; Pissolato Filho, José (Institute of Electrical and Electronics Engineers (IEEE), 2008)
The inclusion of the corona effect in a frequency dependent transmission line model is proposed in this paper. The transmission line is represented through a cascade of π circuits and the frequency dependence of the longitudinal parameters is synthesized with series and parallel resistors and inductors. The corona effect will be represented using the Gary and Skilling-Umoto models. The currents and voltages along the line are calculated by using state-space technique. To demonstrate the accuracy and validity of the proposed frequency dependent line model, time domain simulations of a 10 km length single-phase line response under energization procedure will be presented. ©2008 IEEE.
Keywords: Corona; State space methods; Time domain analysis; Transmission lines; Corona effect; Currents and voltages; Energization; Frequency dependence; Frequency dependent line model; Frequency dependent transmission lines; State-space technique; Time-domain simulations; Transmission line; Bandpass filters; Electric lines; Electromagnetic wave emission; Transmission line theory